О-RADS and ADNEX MR scoring system: standardization of assessment and modern approaches to stratification of ovarian malignancy risks - A. E. Solopova; A. N. Dudina (Акушерство, гинекология и репродукция, 2020)
This article reviews the studies published over the recent 10 years about diagnostic imaging of ovarian lesions (OL). We discuss the current classification systems considering the imaging criteria and the risks of malignancy as well as the ways of optimizing the treatment of patients. There are a number of methods of evaluation and interpretation of diagnostic data obtained using ultrasound as a first line method for OL visualization. To report the results, there is a unified terminology system O-RADS (Ovarian-Adnexal Reporting and Data System) developed specifically for ultrasound examinations. In 2013, the ADNEX MR (adnexal lesions magnetic resonance imaging) scoring system (AMRSS) was developed to standardize magnetic resonance data. That system combines the analysis of both basic-anatomical and functional MR-images and allows one to classify ovarian tumors by the risk of malignancy. Although O-RADS and AMRSS are based on different diagnostic modalities, they complement each other for the diagnostic purpose. In this review, we analyze correlations between the results obtained with these two methods; we also address the possibility of using the above methods in combination in order to pursue a more comprehensive approach to diagnosis of ovarian cancer.